Ventricular function assessment using an ultrafast spoiled gradient echo sequence with an intravascular blood pool contrast agent in pediatric patients - Tayaba Miah; Rithvik Gunda; Gerald Greil; Mohammad Hussain; Qing Zou (PLoS ONE, 2025)
Background Balanced steady-state free processing (bSSFP) MR sequence has long been considered the gold standard method for ventricular function assessment (VFA), and normal values are based on this acquisition. However, bSSFP sequence suffers from susceptibility artifacts due to scenarios such as cardiac implants. The T1-TFE sequence, also known as ultrafast spoiled gradient sequence, is less affected by such susceptibility artifacts. While it is unclear if T1-TFE sequence yields similar VFA results as the bSSFP sequence. Purpose To validate if the T1-TFE sequence, with an intravascular blood pool contrast agent, yields similar results for VFA as the gold-standard non-contrast bSSFP approach, so that the T1-TFE sequence can be used for VFA when bSSFP approach fails. Methods Two sets of images from two different sequences were utilized in this study. T1-TFE (with contrast) scans were used as one while bSSFP-derived images were used as the other. 37 pediatric patients were recruited into this study. Semi-automated software (cvi42) was used to segment and derive ventricular volumes. Image quality was objectively assessed by comparing signal-to-noise (SNR) and contrast-to-noise ratio (CNR) scores. Last, two expert readers provided a subjective analysis of image quality. Paired t-tests were used to assess significant differences in volumetric values (end-diastolic and end-systolic) between T1-TFE and bSSFP sequences. A Bland-Altman analysis evaluated potential bias and agreement between these sequences. Results Ventricular function assessment via volumetric data analysis resulted in no statistically significant differences (P > 0.05), and high R2 values. SNR and CNR scores also presented with no statistically significant differences (P > 0.05), and nearly identical scores (SNR T1-TFE mean: 29.5 ± 3.1, SNR bSSFP mean: 28.8 ± 3.7, CNR T1-TFE mean: 28.8 ± 3.3, CNR bSSFP mean: 28.1 ± 4.0). Image quality assessment via expert subjective image analysis scores is consistent with the data. All Bland-Altman plots show good agreement and reveal no systematic bias or random error. Conclusion T1-TFE sequences in combination with Ferumoxytol allow reliable ventricular function assessment and overcome the limitations of traditional bSSFP MR sequences in this context.